Market Ethics and Private-Law Contractual Practice in Preferential Shares. (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
Some key ethical aspects of the Spanish contractual private-law and administrative regime in force on the so called preferent participations are shown in this paper, particularly under the stand point of the impact of banking network distribution mechanisms of their IPO issues on non-professional banking clients and investors, mainly since 2008.
Keywords: Preferred or Preferential shares. Private-law contracting. Market Ethics